2009
DOI: 10.1152/ajplung.90434.2008
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of urokinase-type plasminogen activator reduces airway remodeling in a murine asthma model

Abstract: Inhalation of urokinase-type plasminogen activator reduces airway remodeling in a murine asthma model. Am J Physiol Lung Cell Mol Physiol 296: L337-L346, 2009. First published December 19, 2008 doi:10.1152/ajplung.90434.2008.-The airway remodeling that occurs in asthma is characterized by an excess of extracellular matrix deposition in the submucosa, hyperplasia/hypertrophy of smooth muscle, goblet cell metaplasia, and accumulation of fibroblasts/myofibroblasts. The urokinase-type plasminogen activator (uPA)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…This study supports previous observations linking the plasmin system with pathogenesis of allergic asthma [8][9][10][11][12][13][14][15][16]. In the present study we demonstrate that, in the airways of allergic asthma patients, allergen exposure leads to up-regulation of both components of the plasmin system: PAI-1 and uPA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study supports previous observations linking the plasmin system with pathogenesis of allergic asthma [8][9][10][11][12][13][14][15][16]. In the present study we demonstrate that, in the airways of allergic asthma patients, allergen exposure leads to up-regulation of both components of the plasmin system: PAI-1 and uPA.…”
Section: Discussionsupporting
confidence: 93%
“…In an animal asthma model either suppression of PAI-1 expression by knockout of the PAI-1 gene or delivery of exogenous uPA leads to decreased airway remodeling and decreased airway hyperresponsiveness [7][8][9]. In humans, genetic variants of uPA and PAI-1 genes are associated with increased risk of allergic asthma [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The induction of PAI-1 expression is related to collagen deposition in murine asthma model [50]. In view of the fact that Smad3 siRNA transfection did not induce the activities of NF-κB or PAI-1 in Smad3 downstream signal cascades in BMMCs, we suggest that cigarette smoke may induce collagen deposition by mast cell activation through TGF-β/Smad signaling pathways.…”
Section: Discussionmentioning
confidence: 97%
“…Enhancing uPA/plasmin activity lessens the airway remodeling in a murine asthma model. 32 This remains the case, even though there is compelling evidence of uPA involvement in tissue remodeling, and uPA has attracted attention as an emerging therapeutic target in cancer. 33 Genetic studies have also shown an essential role of uPA in tissue healing or regeneration.…”
Section: Discussionmentioning
confidence: 99%